Electrical stimulation in the expulsion of Cryphiops caementarius spermatophores according to size and molting stages - Reyes-Avalos, Walter (2022)
The aim of the study was to evaluate the effect of electrical stimulation on the expulsion of Cryphiops caementarius spermatophores according to size and molting stages. Male prawns from 3.0 to 10.8 cm total length, caught in the Lacramarca River (Ancash, Peru) and kept in aquariums (55 L) were evaluated. For spermatophores expulsion, electric shocks of 4 V (n=15), 6 V (n=12) and 8 V (n=6) were applied on the coxopodites of the fifth pair of periopods (1-3 s and for 2-3 times). Spermatophores expulsion was achieved with 4 to 8 V, independent of the size of the prawn, but there was greater expulsion with 6 and 8 V in specimens of 5-8 cm in size and in C, Do and D1 molting. There was no expulsion of spermatophores in molting B prawn with any electrical stimulus.